Supercritical Fluid Carbon Dioxide Sterilization Of Clinical Solid Waste - Hossain, Md. Sohrab (2013)
There is growing awareness on safe handling and management of clinical solid waste. The aim of the present study was to determine an effective sterilization method for safe handling and recycle-reuse of clinical solid waste materials. A preliminary study on the clinical waste management practice was conducted at Hospital Lam Wah Ee, Penang, Malaysia. The management practices encompasses segregation, collection, transportation and require high financial investments. Despite these practices, the infectious risk is still at hand. The existing recycling programs of general solid waste materials remains unchanged of the amount of clinical solid waste generation, its hazard and the disposal cost. In this study, several types of nosocomial and opportunistic pathogenic bacteria have been identified and sterilization of clinical solid waste is requisite to minimize infectious risks to the workers. Comparison on the sterilization efficiency of steam autoclave and supercritical carbon dioxide (SF-CO2) on clinical solid waste was conducted. Steam sterilization inactivation of bacteria depended on temperature and treatment time and types of bacterial species. The most effective experimental condition for the autoclave treatment was found to be temperature 121 0C and 131 0C for the exposure time 60 min and 30 min, respectively. SF-CO2 inactivates the bacteria in clinical solid waste including E. coli, E. faecalis, S. marcescens and S. aureus, B. sphaericus at a relatively lower temperature at 60 0C and moderate pressure of 20 MPa.